A method for treating cancer by introducing a pro-apoptotic gene. - Mohd. Lila, Mohd. Azmi; Phong, Su Fun (2006)

(untitled)
The present invention relates to a method to treat cancer by introducing or delivering a nucleic acid sequence which capable to subsequently induce apoptosis in the treated cancer cells once it is expressed.